Application of cax tools in the design of injection molds - Ziobro, J.; Marciniec, A. (Polimery, 2010)
In this review paper, the application of correlated CAx tools - a multi-aspect terminology used to describe the application of general engineering techniques as well as the computer aid tools for design (CAD), analysis (CAE), production (CAE) etc. has been presented. The fundamental part of the construction process was performed with the aid of the parametrical program Inventor. The verification of the functionality of the form was performed with the MSC.MARC program. The optimal mold-filling capabilities were determined in the Moldflow program. This program was also used to evaluate the influence of geometric parameters of the gating system of the mold on injection pressure and clamp force. Most of these studies were done with special consideration the criterion of minimizing the load of the mold. On the basis of the results of the performed analysis, a quarter of the geometric model of the mold was built using Inventor applications. The applied analysis method together with the MSC.MARC program allowed for the testing of the molds in terms of deformation and also permeability resulting from it. The potential sources of flashes and dangers were also indicated. The effectiveness of mold activity was analyzed taking into consideration, first and foremost, the possibility of jams occurring in the leader pin-guide bushing. On the basis of numerical analysis a construction solution for the leader pin-guide bushing has been proposed which would eliminate this most undesired phenomenon. The most suitable position as well as the required active contact length of this kinematic pair was shown. The complete geometric model of the mold was constructed according to Inventor program on the basis of the models obtained from the performed simulation studies.